2020
DOI: 10.1186/s12955-020-01544-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral contraceptives on the quality of life of women with polycystic ovary syndrome: a crossover randomized controlled trial

Abstract: Background and objective: A limited number of studies have evaluated the effects of oral contraceptives (OCs) on the quality of life (QOL) of polycystic ovary syndrome (PCOS) patients. This study aimed to compare the effects of using OCs containing levonorgestrel (LNG) and those containing desogestrel (DSG), cyproterone acetate (CPA) or drospirenone (DRSP) for 6 months on the QOL with PCOS. Methods: In this crossover randomized controlled 6-arm trial, 200 eligible patients with PCOS scheduled for OC therapy we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Our research did not show any correlation between the use of OCPs and symptoms of depression. However, a previous study suggested that oral contraceptive pills are not indifferent to mental health [ 46 ]. Both positive and negative effects on psychiatric disorders have been reported among women using OCPs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research did not show any correlation between the use of OCPs and symptoms of depression. However, a previous study suggested that oral contraceptive pills are not indifferent to mental health [ 46 ]. Both positive and negative effects on psychiatric disorders have been reported among women using OCPs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies compared oral contraceptives containing drospirenone (DRSP) with the second-generation progestin, levonorgestrel (LNG). [29][30][31][32][33][34][35][36][37] Eight studies evaluated dienogest (DNG)-containing COCs, 29,30,[38][39][40][41][42][43] and one trial assessed nomegestrol acetate (NOMAC). 44 Two studies compared cyproterone acetate (CPA)-containing COCs against other generation progestins.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…• Рекомендуется проводить терапию комбинированными гормональными контрацептивами (КГК): КОК (по АТХ -Прогестагены и эстрогены (фиксированные сочетания)), пластырь, интравагинальное кольцо у пациенток с СПЯ, нарушениями менструального цикла и клиническими проявлениями гиперандрогении (гирсутизм и акне) в качестве терапии первой линии [59][60][61][62][63][64].…”
Section: уур -а (удд -1)unclassified